A new 1-hexyl-3-methylimidazolium tris(pentafluoroethyl)trifluorophosphate ionic liquid based ultrasound-assisted emulsification microextraction for the determination of organic ultraviolet filters in environmental water samples - Ge, D. (2014)
10.1016/j.chroma.2012.06.048